2021
DOI: 10.1093/tas/txab026
|View full text |Cite
|
Sign up to set email alerts
|

Effects of bacterial cultures, enzymes, and yeast-based feed additive combinations on ruminal fermentation in a dual-flow continuous culture system

Abstract: Bacterial cultures, enzymes and yeast derived feed additives are often included in commercial dairy rations due to their effects on ruminal fermentation. However, the effects of these additives when fed together are not well understood. The objective of this study was to evaluate the changes in ruminal fermentation when a dairy ration is supplemented with combinations of bacterial probiotics, enzymes and yeast. Our hypotheses were that ruminal fermentation would be altered, indicated through changes in volatil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
11
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 37 publications
4
11
2
Order By: Relevance
“…The additional nutrient flow of protein increases the amount and quality of protein available in the small intestine, where amino acids are absorbed for use by the animal (Yoon and Stern 1995). Recently, we tested yeast (Saccharomyces cerevisiae) and observed no changes in ruminal fermentation and digestibility (Bennett et al 2021).…”
Section: Yeastmentioning
confidence: 95%
See 1 more Smart Citation
“…The additional nutrient flow of protein increases the amount and quality of protein available in the small intestine, where amino acids are absorbed for use by the animal (Yoon and Stern 1995). Recently, we tested yeast (Saccharomyces cerevisiae) and observed no changes in ruminal fermentation and digestibility (Bennett et al 2021).…”
Section: Yeastmentioning
confidence: 95%
“…Additionally, increases in the proportion of propionate reduce the amount of methane produced, which is both an energetic loss to the animal and an environmental health concern (Jeyanathan et al 2014). Recently, we tested Lactobacillus animalis, Propionibacterium freudenreichii, Bacillus lichenformis, Bacillus subtillis, and Enterococcus faecium and observed no changes in ruminal fermentation and digestibility (Bennett et al 2021). We have also evaluated Lactobacillus plantarum and observed a reduction in ruminal ammonia, which may represent an improvement in ruminal nitrogen utilization (Monteiro et al 2020).…”
Section: Bacteriamentioning
confidence: 99%
“…The yeast stimulated the growth of M. elsdenii, which converted lactate into C 3 and C 4 [6,35]. However, the inclusion of yeast in the diet increased C 4 concentration, but did not result in major changes in ruminal fermentation [49].…”
Section: Ruminal Volatile Fatty Acid (Vfa) Profiles and Methane (Ch 4...mentioning
confidence: 99%
“…This result concurred with findings of Sousa et al [33], who reported that the addition of yeast significantly increased the relative population of R. flavefaciens. The addition of DY increased the growth of cellulolytic bacterial populations, particularly R. flavefaciens and F. succinogenes, while limiting the growth of the lactate-producing bacterium (S. bovis) and increasing rumen fermentation consistency [49]. Ding et al [51] found that adding yeast enhanced the number of bacteria, fungi, protozoa, lactate-utilizing bacteria, and the rate of fiber degradation.…”
Section: Ruminal Volatile Fatty Acid (Vfa) Profiles and Methane (Ch 4...mentioning
confidence: 99%
“…This allows more hydrolysis to occur throughout the rumen, carrying on a cycle of more substrate increasing the growth of bacteria, which in turn increases endogenous bacterial enzyme secretions (McAllister et al 2001). Recently, we tested a hemicellulose, xylanase, and amylase mixture, and observed only minor changes in ruminal fermentation, with no increase in ruminal digestibility (Bennett et al 2021). While there is not generally an increase in the extent of nutrient digestibility with the inclusion of enzymes in the diet, there is an increase in the rate of nutrient digestibility.…”
Section: Rumen Effectsmentioning
confidence: 99%